Parametric Study for Runner Modifications of Die Casted Part with Venting Systems - Ibrahim, M.D.; Jendia, J.; Kashiwabara, Y.; Sunami, Y. (International Journal of Integrated Engineering, 2023)
High-pressure die casting (HPDC) is a process used for creating complex components by injecting the molten metal inside the cavity at high pressure. Failure in die casting may reduce product mechanical properties, surface quality, and life cycle. In this paper, the die-casting process of an inspection instrument – test piece is investigated for parametric study and Computational fluid dynamics (CFD) analysis. Parameters used in the die-casting process are important since it affects the molten flow quality inside the cavity. Thus, a parametric study is done to investigate the optimum parameter use in the die-casting process of the test piece. Runner gating system design is also one of the important criteria to maintain the quality of products. This paper also investigated the effect of runner gating system design optimization in reducing gas porosity. The CT scan of the sample mold is included to compare the relationships between gas porosity occurrence with CFD results. This paper proposed a new runner design named outward curvature runner with an air vent that can improve velocity and temperature distributions in reducing die-casting defects. In addition to that, air vents are installed to extend the volume and promote higher suction, to eliminate gas bubbles entrapment inside the cavity.